2010
DOI: 10.1007/s11881-010-0045-6
|View full text |Cite|
|
Sign up to set email alerts
|

Contribution of discourse and morphosyntax skills to reading comprehension in Chinese dyslexic and typically developing children

Abstract: This study aimed at identifying important skills for reading comprehension in Chinese dyslexic children and their typically developing counterparts matched on age (CA controls) or reading level (RL controls). The children were assessed on Chinese reading comprehension, cognitive, and reading-related skills. Results showed that the dyslexic children performed significantly less well than the CA controls but similarly to RL controls in most measures. Results of multiple regression analyses showed that word-level… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
65
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 59 publications
(72 citation statements)
references
References 66 publications
5
65
2
Order By: Relevance
“…In general, dyslexic children in this study performed significantly poorer than their CA controls but similarly to their RL controls in most of the language measures except semantic skills and syntactic skills on multiple modifiers. Such findings have been reported repeatedly in prior studies (Chik et al , ; Ho, Chan, Tsang, & Lee, 2002) and used as evidence for the developmental lag interpretation of reading disabilities (Backman, Mamen, & Ferguson, ; Goswami & Bryant, ; Stanovich, Nathan, & Vala‐Rossi, ). According to the interpretation, reading‐disabled children's failure in reading could be attributed to a lag in the development of reading‐related skills such as phonological processing skills, and thus, poor readers are expected to perform like their RL counterparts in reading and reading‐related tasks (Beech & Harding, ).…”
Section: Discussionsupporting
confidence: 72%
See 2 more Smart Citations
“…In general, dyslexic children in this study performed significantly poorer than their CA controls but similarly to their RL controls in most of the language measures except semantic skills and syntactic skills on multiple modifiers. Such findings have been reported repeatedly in prior studies (Chik et al , ; Ho, Chan, Tsang, & Lee, 2002) and used as evidence for the developmental lag interpretation of reading disabilities (Backman, Mamen, & Ferguson, ; Goswami & Bryant, ; Stanovich, Nathan, & Vala‐Rossi, ). According to the interpretation, reading‐disabled children's failure in reading could be attributed to a lag in the development of reading‐related skills such as phonological processing skills, and thus, poor readers are expected to perform like their RL counterparts in reading and reading‐related tasks (Beech & Harding, ).…”
Section: Discussionsupporting
confidence: 72%
“…More importantly, in a study of modelling the relationship between cognitive–linguistic skills and reading in Chinese, Yeung et al () reported that syntactic word order skills accounted for unique variance in both sentence and passage reading comprehension controlling for the effects of word reading and other cognitive skills. Chik et al () reported that Chinese dyslexic children performed significantly less well in the tasks of oral vocabulary, word semantics, word order and discourse than their age‐matched typically developing counterparts and both oral vocabulary and word semantics made significant prediction to reading comprehension performance except for the word order task. It is noteworthy that in another study, Chik et al () did find significant predictive effect of word order to sentence comprehension among Chinese typically developing second graders.…”
Section: Introductionmentioning
confidence: 82%
See 1 more Smart Citation
“…The greater ability to access and manipulate phonemic knowledge in higher-elision RD children did not translate to improved cross-modal mapping, consistent with the finding that orthographic information is less likely to intrude on phonological tasks for RD readers (Landerl et al, 1996). RD interventions often involve extensive phonological awareness training (Hulme et al, 2012; Youman and Mather, 2012), but the emphasis on phonological awareness may be at the expense of learning to map between modalities. If the critical deficit in dyslexia is in the mapping from orthography to phonology, orthographic knowledge will be less likely to facilitate the development of phonological awareness, and the two skills will be decoupled.…”
Section: Discussionmentioning
confidence: 99%
“…For example, individuals with dyslexia are impaired in basic motor skills while performing an additional secondary task (Nicolson & Fawcett, 1990; Yap & van der Leij, 1994). Other studies reveal that individuals with dyslexia are impaired on motor adaptation (Brookes, Nicolson, & Fawcett, 2007) and implicit motor sequential learning tasks (Bennett, Romano, Howard, & Howard, 2008; Du & Kelly, 2012; Howard et al, 2006; Stoodley et al, 2006; Stoodley, Ray, Jack, & Stein, 2008; Vicari et al, 2005). Furthermore, procedural motor learning skills of individuals with dyslexia are less stable, more prone to interference (Gabay, Schiff, & Vakil, 2012b) and consolidate less effectively (Gabay, Schiff, & Vakil, 2012a).…”
Section: Introductionmentioning
confidence: 99%